Cavitary pulmonary tuberculosis with COVID-19 coinfection. (2020) - Yousaf, Zohaib; Khan, Adeel A.; Chaudhary, Haseeb A.; Mushtaq, Kamran; Parengal, Jabeed; Aboukamar, Mohamad; Khan, Muhammad Umair; Mohamed, Mouhand F.H.
Abstract: The COVID-19 pandemic has strained the healthcare system worldwide, leading to an approach favoring judicious resource allocation. A focus on resource preservation can result in anchoring bias and missed concurrent diagnosis. Coinfection of Mycobacterium tuberculosis (TB) and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has implications beyond morbidity at the individual level and can lead to unintended TB exposure to others. We present six cases of COVID-19 with newly diagnosed cavitating pulmonary tuberculosis to highlight the significance of this phenomenon and favorable outcomes if recognized early.